Timing of surgery and adjuvant radiation therapy for sinonasal malignancies: Effect of surgical approach. Issue 10 (11th July 2019) - Xiao, Roy; Joshi, Rohan R.; Husain, Qasim; Cracchiolo, Jennifer R.; Lee, Nancy; Tsai, Jillian; Yu, Yao; Chen, Linda; Kang, Jung J.; McBride, Sean; Riaz, Nadeem; Roman, Benjamin R.; et al.
Abstract: Background: Timely postoperative radiation therapy (RT) within 50 days of surgery for head and neck cancers provides a survival advantage. Methods: Using the National Cancer Database, we performed a propensity score‐matched analysis comparing patients undergoing open or endoscopic surgery for squamous cell carcinoma (SCC) of the nasal cavity and paranasal sinuses from 2010 to 2015. Results: Among 168 pairs, patients undergoing endoscopic surgery had shorter time to surgery (24.2 vs 36.7 days, P  < .001) and shorter postoperative time to RT (PTTR, 51.2 vs 58.4 days, P = .02). On multivariable linear regression, endoscopic surgery predicted shorter PTTR (β = −7.6, P = .01). Using the Kaplan‐Meier method, patients in the longest PTTR quartile had decreased overall survival (OS; Q1 vs Q4, 3‐year OS 76.5% vs 53.3%, P = .007), a durable finding when adjusted for covariates (Q1 vs Q4, HR 0.50, P = .008). Conclusions: Patients undergoing endoscopic surgery for sinonasal SCC experience shorter PTTR. Shorter PTTR is associated with extended OS.